2014
DOI: 10.4269/ajtmh.13-0423
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Risk Factors for Severe Fever with Thrombocytopenia Syndrome Virus Infection in Jiangsu Province, China, 2011

Abstract: Abstract. Severe fever with thrombocytopenia syndrome (SFTS), which is caused by a novel bunyavirus, is an emerging infectious disease in China. In 2011, this new virus was designated as severe fever with thrombocytopenia syndrome virus (SFTSV). The aim of the present study was to determine the seroprevalence and risk factors of SFTSV infection. The investigation was conducted among the general population in Jiangsu Province, China in 2011. A total of 2,510 serum samples were collected. Testing by enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 10 publications
1
42
1
Order By: Relevance
“…The positive rate in this study was similar to the reported percentage (3.3%) recorded in Shandong Province 14 . However, it was much higher than that reported in Jiangsu (0.44%), lower than that in Shanxi (4.7%) 15,16 . The discrepancy may be attributed to the season of collection, population size, geographic climatic factors and different methods.…”
Section: Discussioncontrasting
confidence: 66%
“…The positive rate in this study was similar to the reported percentage (3.3%) recorded in Shandong Province 14 . However, it was much higher than that reported in Jiangsu (0.44%), lower than that in Shanxi (4.7%) 15,16 . The discrepancy may be attributed to the season of collection, population size, geographic climatic factors and different methods.…”
Section: Discussioncontrasting
confidence: 66%
“…26 An epidemiological study further implicated goat ownership and exposure to Haemaphysalis longicornis ticks as risk factors for SFTSV infection in Jiangsu Province, China. 10 Goats were not assessed for HRTV-neutralizing antibodies in this study as this species of domesticated animal was absent in our study sites.…”
Section: Discussionmentioning
confidence: 97%
“…7 HRTV is genetically most closely related to a recently discovered tick-borne virus infecting humans in China known as severe fever with thrombocytopenia syndrome virus (SFTSV), 1,8,9 which is believed to be acquired by larval ticks feeding on viremic domestic farm animals, transstadially passaged to the nymphal stage and transmitted to humans by blood-feeding nymphs. 10 Because of the tick exposures reported by both of the original human cases in 2009, 1 the detection of HRTV-infected nymphal ticks in 2012 from one of the human case residences and a nearby conservation area, 7 and the tick-associated transmission of the closely related SFTS virus, 11 HRTV was presumed to be maintained by ticks and nonhuman vertebrate amplification host(s). The lone star tick, the putative vector, is known to feed on a wide range of medium-and large-sized vertebrate hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Because the primary mode of transmission by which SFTSV infects humans is a bite by a SFTSV-infected tick, an occupational risk was noted for individuals working in farms as well as for those in contact with domestic and/or wild animals (12)(13)(14). SFTSV is known to circulate in Japan because patients with SFTS are being notified (6) because the SFTSV genome is detected in several tick species and a high prevalence of anti-SFTSV antibody seropositivity was observed among deer, wild boars, dogs, and raccoon dogs (15).…”
Section: Discussionmentioning
confidence: 99%